Chromolaena odorata Linn leaf extract - Geothermal versus nongeothermal: Phytochemical, antioxidant, and cytotoxicity screenings - Azzaki Abubakar; Hanifah Yusuf; Maimun Syukri; Rosnani Nasution; Rinaldi Idroes (Wolters Kluwer Medknow Publications, 2023)
Chromolaena odorata Linn, a popular yet underutilized ethnomedicinal plant, is hypothesized to possess higher bioactive phytoconstituents when it grows in geothermal areas. In this study, the comparison of ethanolic extract from geothermal and nongeothermal C. odorata leaves was carried out based on the phytochemical profile, antioxidant activity, and cytotoxicity. The leaf extracts were produced from a maceration using ethanol 96%, where the products were identified using reagents and gas chromatography-mass spectrometry (GC-MS). Antioxidant activities of both samples were measured based on their 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activities. Cytotoxicity was determined by brine shrimp lethality test using Artemia salina. Phenols were found to be more abundant in geothermal sample based on the qualitative screening and GC-MS analysis (i.e. higher relative abundance of phytol - 3.97%). DPPH antioxidant was higher in geothermal sample than in nongeothermal sample (median inhibitory concentration =13.04 ± 3.35 mg/L vs. 41.09 ± 4.13 mg/L, respectively). Geothermal sample was noncytotoxic (median lethal concentration [LC50] =2139.30 mg/L), whereas the nongeothermal sample had low cytotoxicity (LC50 = 491.48 mg/L). Taken altogether, geothermal C. odorata leaves contain higher bioactive compounds with potent antioxidant activities.